Relationship between in ovo feeding and eggshell temperature of breeder eggs during incubation - Okai, Maxwell Ansong; Kruenti, Francis; Hamidu, Jacob Alhassan; Tona, Kokou; Hai, Lin (Frontiers in Animal Science, 2025)
The hatching egg biologically provides protection and nutrition for its embryo during the pre-incubation and incubation periods. However, in cases in which an egg’s nutritional composition is inadequate to support the development and growth of the embryo, the embryo may die. To avoid this, nutrients can be artificially introduced into the hatching egg. In ovo feeding introduces nutrients directly to the embryo to enhance its development and hatchability. The technique, when properly implemented, maximizes nutrient absorption and improves the economic traits of growing birds and their end products. However, several studies have also reported negative effects of the technique on the temperature of the eggshell indicating its significant effect on embryonic development, eggs’ hatching ability, and the quality and growth of chicks. The application of eggshell cooling procedures and external devices to mitigate the increase in eggshell temperature during in ovo feeding has been explored. This technology can be adopted under conditions of nutrient deficiency in eggs for specific poultry breeds for enhanced post-hatch growth. This review examined and provides a comprehensive understanding of the relationship of in ovo feeding with eggshell temperature, shedding light on the potential implications of the former for enhanced hatchery operations and poultry production. It also highlights the factors that influence the effect of in ovo feeding on eggshell temperature with suggested solutions and research gaps that need to be investigated in the future.